PENGEMBANGAN E-MODUL SEBAGAI SUMBER BELAJAR PRAKTEK SHOLAT PADA MATA PELAJARAN PAI KELAS VII DI SMP NEGERI 2 SULIKI KABUPATEN LIMA PULUH KOTA - Ika Rahim; Iswantir Iswantir; Junaidi Junaidi; Salmi Wati (KOLONI, 2022)
This research is motivated by the rapid development of increasingly sophisticated technology in the era of globalization, so educators are also required to have IT skills that can support learning and make teaching materials that are more creative and innovative. However, at SMP N 2 Suliki, the learning of Islamic Religious Education still does not take advantage of the sophistication of the available technology. This research is a development research which consists of three stages, namely: the definition stage, the design stage and the develop stage. The research instrument used a validation sheet and a questionnaire. The module was validated by three validators, namely one media lecturer, one Islamic religious education lecturer, and one Islamic religious education teacher. At the practicality stage and the effectiveness of the e-module as a source of learning to practice prayer, it was tested on 26 seventh grade students of SMP N 2 Suliki. Based on the results of data analysis that has been carried out, it can be concluded as follows: (1) The results of the validation of the e-module as a learning resource for prayer practice materials developed for class VII SMP N 2 Suliki are valid with a percentage of 85.3%. (2) The results of the trial on the practicality of the e-module as a learning resource for prayer practice materials that were developed showed the results of the teacher's practicality of 90.2% and the practicality of students of 85.4% with a very practical category that can be used in the learning process. (3) The results of the effectiveness trial on student learning outcomes with a correlation of 84% with the category of being very effective and giving a strong influence in the learning process. Keyword: Development, E-Module, Prayer Practice, SMP N 2 Suliki